CHINA POP LOVE, PATRIOTISM AND THE STATE IN CHINA’S MUSIC SPHERE - Steen, Andreas (Temp - tidsskrift for historie, 2013)
ABSTRACT China Pop: Love, Patriotism and the State in China’s Music Sphere Popular culture in China is a dynamic and contested sphere of activities, conflicts and negotiations. The effects of globalization as well as new media and communication technologies challenge the authorities and enrich cultural cr eativity. Today, the state maintains its omnipresence in this cultural sector while promoting a policy of dialogue, integration and exclusion. Cooperation with the state is attractive because it is rewarded with unlimited access to official media, audiences and commercial success. The article focuses on recent trends in China’s most important genres of popular music: Mandopop, (red) mainstream music and rock music. It argues that the state’s success in raising the popularity of the mainstream is based on its constant promotion, patriotic education, a general pride in China’s strength, nationalism and – equally important – adaptation and the commercial attractiveness of the Chinese market. Mandopop and rock music are carefully integrated, while national/international artists and companies engage in self-censorship and thereby support the mainstream ideology. The transformation of Chinese pop reflects necessary steps towards cultural liberalism, yet it is based on conscious efforts of control and guidance in order to promote a new Chinese national popular culture.